Percepción de los turistas y stakeholders sobre los paisajes culturales y la sustentabilidad turística en la ciudad de Iquitos - Rengifo Ruiz, Vania (2024)
The research thesis “Perception of tourists and stakeholders on cultural landscapes and tourism sustainability in the city of Iquitos” was developed with the objective of knowing how tourists and stakeholders perceive cultural landscapes based on tourism sustainability in the city. . The method was applied with a quantitative applied research approach. It is a non-experimental descriptive design, with a non-probabilistic sample of 35 surveys applied to tourists and 25 stakeholders from different institutions that are related to tourist activity. The data collection instrument applied to tourists and stakeholders consisted of three alternatives: low, medium and high, who accepted informed consent. The results of the study for tourists referred to the Cultural Landscapes variable as: Panorama and culture, quality of the Urban Landscapes and Scenarios, of the stakeholders of the Tourism Sustainability variable: economic, social and environmental pillar. With the hypothesis it has been shown that the assessment of Cultural Landscapes is not satisfactory with the sustainability of the three pillars of development.